The Influence Of Work Environment On Employee Work Productivity At Bank Bjb Syariah Sumedang - Fauzaan, Wendy Rahayau; Anggini, Megah Dewi; Nurfauzia, Fadila (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2026)
This study is entitled The Influence of Work Environment on Employee Work Productivity at Bank BJB Syariah Sumedang. This study uses a quantitative method, conducted with an observation method using the entire population of 32 people. The results of this study indicate that the Work Environment is 3059 (good) with an average of 79.66%, Employee Work Productivity is 1653 (very good) with an average of 89.09%. Furthermore, the magnitude of the relationship between the Work Environment and Employee Work Productivity at Bank BJB Syariah Sumedang is 92,2% (very strong). The results of the t-test> t-table or 9.469> 1.68595, it can be said that there is a positive influence between the Work Environment and Employee Work Productivity at Bank BJB Syariah Sumedang, the hypothesis can be accepted.